2015
DOI: 10.3168/jds.2015-9446
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Concentrations of nonesterified fatty acids and β-hydroxybutyrate in dairy cows are not well correlated during the transition period

Abstract: The objective was to use longitudinal data of blood nonesterified fatty acids (NEFA) and β-hydroxybutyrate (BHBA) concentrations to describe the relationship between NEFA and BHBA in dairy cows during the periparturient period. Blood NEFA and BHBA concentration data collected from d 21 prepartum to 21 postpartum for 269 multiparous Holstein cows were selected from 4 different studies carried out within our research groups. Overall, NEFA concentrations were increased beginning near parturition with a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 25 publications
11
57
0
1
Order By: Relevance
“…As both serum NEFA and BHB concentrations are measures of adipose tissue mobilization (Otter, 2013), these 2 serum concentrations theoretically should be consistent. However, this discrepancy in serum NEFA and BHB concentrations preceding calving is consistent with McCarthy et al (2015) who demonstrated a weak relationship between serum NEFA and BHB concentrations and concluded that a higher concentrations of one metabolite does not necessitate a higher concentration of the other.…”
Section: Prepartum Intake Energy Balance and Body Tissue Changessupporting
confidence: 86%
“…As both serum NEFA and BHB concentrations are measures of adipose tissue mobilization (Otter, 2013), these 2 serum concentrations theoretically should be consistent. However, this discrepancy in serum NEFA and BHB concentrations preceding calving is consistent with McCarthy et al (2015) who demonstrated a weak relationship between serum NEFA and BHB concentrations and concluded that a higher concentrations of one metabolite does not necessitate a higher concentration of the other.…”
Section: Prepartum Intake Energy Balance and Body Tissue Changessupporting
confidence: 86%
“…The correlation between FFA and BHB is especially difficult to explain. Although some cows with normal BHB levels have high FFA levels, other cows with normal FFA levels have high BHB levels, demonstrating unexplained interindividual variability within a group of cows McCarthy et al, 2015). This interindividual variability represents the interindi-vidual ability of cows to adapt to the altered metabolic challenge of lactation and demonstrates the limitations of monitoring metabolism based on a single metabolic indicator (Ingvartsen et al, 2003;Bjerre-Harpøth et al, 2012;Moyes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, regarding the response of NEFA to the IVGTT, no differences in the metabolism of BHBA after glucose infusion were observed between the 2 groups. However, concentrations of NEFA and BHBA do not correlate well, because the synthesis of ketone bodies does not depend only on energy balance. Therefore, the greater decrease in serum NEFA may not directly translate to a greater decrease in the concentration of BHBA.…”
Section: Discussionmentioning
confidence: 97%